Fast Fluoroalkylation of Proteins Uncovers the Structure and Dynamics of Biological Macromolecules - Fojtík, Lukáš; Fiala, Jan; Pompach, Petr; Chmelík, Josef; Matoušek, Václav; Beier, Petr; Kukačka, Zdeněk; Novák, Petr (Journal of the American Chemical Society, 2021)
Covalent labeling of proteins in combination with mass spectrometry has been established as a complementary technique to classical structural methods, such as X-ray, NMR, or cryogenic electron microscopy (Cryo-EM), used for protein structure determination. Although the current covalent labeling techniques enable the protein solvent accessible areas with sufficient spatial resolution to be monitored, there is still high demand for alternative, less complicated, and inexpensive approaches. Here, we introduce a new covalent labeling method based on fast fluoroalkylation of proteins (FFAP). FFAP uses fluoroalkyl radicals formed by reductive decomposition of Togni reagents with ascorbic acid to label proteins on a time scale of seconds. The feasibility of FFAP to effectively label proteins was demonstrated by monitoring the differential amino acids modification of native horse heart apomyoglobin/holomyoglobin and the human haptoglobin-hemoglobin complex. The obtained data confirmed the Togni reagent-mediated FFAP is an advantageous alternative method for covalent labeling in applications such as protein footprinting and epitope mapping of proteins (and their complexes) in general. Data are accessible via the ProteomeXchange server with the data set identifier PXD027310.
Keywords: alkylace; Animals; konformace proteinů; myoglobin; represorové proteiny; Humans; hmotnostní spektrometrie; hemoglobiny; Mass Spectrometry; Hemoglobins; Hydrocarbons, Fluorinated; Escherichia coli Proteins; Alkylation; fluorované uhlovodíky; proteiny z Escherichia coli; Horses; zvířata; koně; Repressor Proteins; lidé; haptoglobiny; Myoglobin; Escherichia coli; Protein Conformation; Haptoglobins